Effective use of nano-carbons in controlling the electrical conductivity of epoxy composites. (20th January 2021) - Poornima,; Rashmi,; Sundara Rajan, J.
Abstract: Glass fiber reinforced epoxy composites were fabricated using MWCNT and GNP fillers, individually and in combination. The objective of combining the two conductive fillers was to enhance the electrical conductivity of the composites. The DC and AC conductivity measurements were carried out to assess the influence of individual fillers and their combinations on the electrical conductivity. High DC conductivity of 3.1 × 10 −3 S/m and AC conductivity of 1.31 × 10 −2 S/m at 8 MHz were observed, at 2 wt% of MWCNT and 3 wt% of GNP and the values were significantly reduced below 3 wt% of GNP. The observed increase in electrical conductivity is attributed to low contact resistance (299.85Ω) of fillers, reduced tunneling resistance (5.35 × 10 9 Ω) and tunneling distance (1.65 nm) of the composites. The DC and AC conductivity, contact resistance, tunneling resistance and tunneling distance showed reduced dependence on temperature. The AC conductivity of the hybrid composites follows power law. The cut-off frequency of composites was 200 kHz at 3 wt% of GNP and 2 KHz with reduction in weight percentage of GNP. In composite with 2 wt% of MWCNT and 3 wt% of GNP, validity of the percolation model is established. Graphical abstract: Image 1